Association between proton pump inhibitors and hepatic encephalopathy: A meta-analysis. Issue 17 (April 2017) - Bian, Jin; Wang, Anqiang; Lin, Jianzhen; Wu, Liangcai; Huang, Hanchun; Wang, Shanshan; Yang, Xiaobo; Lu, Xin; Xu, Yiyao; Zhao, Haitao
Abstract: Background & aims: Several studies have shown that proton pump inhibitors (PPIs) use can increase the risk of developing hepatic encephalopathy (HE) in patients with liver dysfunction. However, no definite conclusion is drawn because of study design limitations. Therefore, we conducted a meta-analysis to explore the association between PPIs and HE. Methods: We searched PubMed, EMBASE, and the Cochrane Library from inception until November 2016. Data from the identified studies were combined using a random effects model, and odds ratios (ORs) were calculated. Results: Three case-control studies were included. Compared with nonusers, hepatic insufficiency patients receiving PPIs therapy had a significantly increased risk of developing HE (OR = 1.76, 95% CI: 1.15–2.69), with notable heterogeneity ( I 2 = 61.4%, P = .075) and publication bias. No relevance was found between PPIs and HE after using the trim and fill method (OR = 1.360, 95%CI: 0.909–2.035, P = .135). Conclusions: PPIs are associated with a higher risk of HE among patients with chronic and acute liver dysfunction. A final conclusion cannot be drawn because of the limited number of studies and a lack of prospective studies.